2017
DOI: 10.1016/j.jconrel.2017.03.384
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric nanoparticles as cancer-specific DNA delivery vectors to human hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third most deadly cancer in the US, with a meager 5-year survival rate of less than 20%. Such unfavorable numbers are closely related to the heterogeneity of the disease and the unsatisfactory therapies currently used to manage patients with invasive HCC. Outside of the clinic, gene therapy research is evolving to overcome the poor responses and toxicity associated with standard treatments. The inadequacy of gene delivery vectors, including poor intracellular delivery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Thus, it becomes very important to identify the molecular mechanism and biological pathway underlying cellular disturbance and toxicity of NP in target cells and tissues. Recent in vitro studies demonstrated that gene expression profiling combined with cellular and biochemical responses has provided a direct assessment of cellular perturbation and potential NP toxicity [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it becomes very important to identify the molecular mechanism and biological pathway underlying cellular disturbance and toxicity of NP in target cells and tissues. Recent in vitro studies demonstrated that gene expression profiling combined with cellular and biochemical responses has provided a direct assessment of cellular perturbation and potential NP toxicity [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of acid lysosomes has been proved to achieve the gene release from nanoparticles within a few hours during immune cell‐mediated cell uptake process ( Figure a). [ 46 ] Due to these advantages, Tsai et al. first synthesized PBAE by Michael addition reaction to form complex adjuvants with CpG, which showed the targeting effect and immune stimulation on tumor cells (Figure 3b).…”
Section: Structural Designs Of Polymeric Nonviral Gene Delivery Systemsmentioning
confidence: 99%
“…Reproduced with permission. [ 46 ] Copyright 2017, Elsevier Inc. b) Synthetic schematic illustration of PBAE/CpG DNA polyplex. Reproduced with permission.…”
Section: Structural Designs Of Polymeric Nonviral Gene Delivery Systemsmentioning
confidence: 99%
“…Taking advantage of membrane receptors on hepatic stellate cells, liver-targeted gene delivery for hepatic fibrosis has been attempted using the mannose 6-phosphate/insulin-like growth factor-II receptor [132][133][134], integrins [135], high-affinity membrane receptor for retinol-binding protein, and the galactosyl receptor as targets [101]. Target-specific gene delivery is a desirable feature, and polymeric nanoparticles [131] targeting cancer-specific DNA have shown promising anti-tumor effects in vitro and in vivo [136]. A cationic solid lipid nanoparticle also showed effective inhibition of HCC growth by delivering shRNA for the NURP gene [137], and similarly, siRNA to PLK1 gene delivered by chitosan nanoparticles efficiently suppressed HCC cell growth both in vitro and in vivo [138].…”
Section: Non-viral Gene Delivery Using Chemicalsmentioning
confidence: 99%